IN-VITRO ASSESSMENT OF SOME FUNGICIDES FOR THE MANAGEMENT OF SUDDEN DEATH IN MANGO - M. Ismail; G. Y. Dahar; J. A. Tariq; R. M. Memon (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2018)
Mango production in Pakistan has faced enormous losses due to the sudden death malady. It has reduced the farm income significantly. To devise an effective control strategy for this disease, present work was carried out to evaluate the In-Vitro efficacy of fungicides. In this experiment five fungicides including, thiophenate methyl, radomill, score, alliette, and carbendzim were tested at four concentrations i.e. 5, 10, 20 and 40 ppm with three replications under completely randomized design. The results of this study showed that all fungicides significantly inhibited the mycellial growth of Ceratocystis fimbriata as compared to control. Thiophenate methyl was the only fungicide that was effective at its lower concentrations 5 and 10 that showed overall 92.02% mean mycellial inhibition followed by carbendzim which produced 74.84% inhibition as a whole. All other fungicides, score alliette and radomil proved very effective at their higher doses i.e. 20 ppm and 40 ppm and showed significant reduction in mycellial growth. These results suggest that the use of thiophenate methyl and carbendzim can be very useful for the management of sudden death in mango.